2010
DOI: 10.5001/omj.2010.83
|View full text |Cite
|
Sign up to set email alerts
|

Serum γ-glutamyltransferase as Oxidative Stress Marker in Pre-and Postmenopausal Iraqi Women

Abstract: Serum γ-glutamyltransferase may be considered as an index of oxidative stress associated with menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 10 publications
0
10
0
4
Order By: Relevance
“…Increased activity of GGT may be linked to greater oxidative stress. Therefore, the relationship between various diseases and GGT levels has been investigated in several studies [7][8][9][10][11]. A large Austrian study showed for the first time the prognostic value of GGT with regard to fatal events caused by congestive heart failure (CHF) in apparently healthy subjects [12].…”
Section: Introductionmentioning
confidence: 99%
“…Increased activity of GGT may be linked to greater oxidative stress. Therefore, the relationship between various diseases and GGT levels has been investigated in several studies [7][8][9][10][11]. A large Austrian study showed for the first time the prognostic value of GGT with regard to fatal events caused by congestive heart failure (CHF) in apparently healthy subjects [12].…”
Section: Introductionmentioning
confidence: 99%
“…Old age is well known as an important risk factor for many kinds of malignancies. Several authors have reported that the serum γ‐GTP level is influenced by oxidative stress (Abdul‐Rasheed et al., ), and oxidative stress with the release of reactive oxygen species is likely to contribute to the development of both NASH and HCC (Hashimoto and Tokushige, ). Oxidative stress may favor tumorigenesis by promoting inflammation and cell proliferation, or it may directly induce cancer‐promoting gene mutations (Hu et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…These grains release sugar slowly in the blood and also diminish the glucose absorption 57,58 . These grains have also been demonstrated to exhibit beneficial effects on cholesterol levels, which is also due to their high dietary fibre and phytochemical content.…”
Section: Fig 7: Effect Of Selected Minor Millets On Gamma Glutamyl Tmentioning
confidence: 99%